Variações morfológicas nas flores de Byrsonima intermedia (MALPIGHIACEAE) e seu impacto no valor adaptativo da espécie: polinização e produção de frutos - Carvalho, Ana Carolina Monetta de (2015)
For plants which rely on biological pollination, floral traits related to pollination can include tactile, olfactory and visual cues and color, shape and odor or combinations of these cues can be used to identify flowers as source of rewards. One of the components that attract pollinators is symmetry, used to discriminate flowers with different levels of rewards. Symmetry can be altered by the activity of floral herbivores, capable of interfering on pollinator visitation rate or alter pollination efficacy. Malpighiaceae species are known to offer pollen and oil to their floral visitors and compose an important family on Brazilian savannah (Cerrado), one of the most degraded ecosystems in the world. The aim of this study was to: a) observe the relation between natural floral symmetry and floral rewards and b) assess pollinator discrimination of experimentally asymmetrical flowers, simulating floral herbivory, and its effects over pollination and fruit set. Data collection was performed in a Cerrado area inside Clube Caca e Pesca Itororo de Uberlandia, from September 2013 to July 2014. Natural floral symmetry and floral rewards were observed in flowers of 24 bushes of Byrsonima intermedia (Malpighiaceae), in which 3 inflorescences were bagged in pre-anthesis phase and three flowers from each inflorescence had their measures taken. The width of right and left sides of the standard petal was measured as well as the length of proximal petals from the central longitudinal axis . The distance of the apex of standard petal to the distal petals was also measured. Each measured flower was then used to the quantification of elaiophores oil volume with a capillary tube and pollen grain quantification, dyed with Acetic Carmin. On the same plants, we chose four plants that had 10% of petal area removed, on standard, proximal or distal petal and four control plants, which were not manipulated. These flowers were followed to fructification and the seeds were placed in gerbox boxes over germination paper. There were no statistical differences between oil quantity and floral symmetry (r= -0.1407, df= 22, p= 0.5118) as well as pollen quantity (r= -0.0079, df= 22, p= 0.9707), which indicates that, for this particular plant, symmetry is not a reliable sign of floral rewards. There was statistical differences in the proportion of fruits formed from control and treatment groups (X²=91,147, gl=3, p<0,01), but not among treatments (X²=2,026, gl=2, p=0,363), what suggests that petal manipulation have an effect on pollinator visitation, but the point of manipulation is not that significant.